DIGITIZATION OF TRADITIONAL BARIO SALT MAKING BASED ON INTERDISCIPLINARY AND VISUAL EXPERIENCE APPROACH - Yakup, Mohd Rafee; Sylvester Wielding, Jussem; Hishamuddin, Siri; Mohamad zamhari, Abol Hassan (Universiti Sultan Zainal Abidin, 2022)
This article describes the process of digitizing traditional methods of Bario salt extraction based on documentation and experiences during a field trip to Pa'Umor, Bario, Sarawak. The process of making salt is described in an orderly manner, beginning with the extraction of the salt water, and ending with the packing process. Bario salt is extracted from a salt spring by boiling the brine in a large pot until the salt forms a gray layer, and then collecting the salt from the bottom. This process is still practiced today. However, the production of Bario salt is not widely known because it is a lengthy and laborious process. Moreover, the conventional methods of information transfer are no longer relevant to current technological developments. Therefore, through an interdisciplinary and visual experience approach, all images are recorded in a digital documentation using the latest digital tools and then analyzed through the art of formalism. The result is a short video production and digital interactive poster called ID-Poster that uses the augmented reality application. It is hoped that this article will provide new ideas and visual insights that can help in promoting rural tourism.